Understanding the Growth and Properties of Sputter‐Deposited Phase‐Change Superlattice Films - Simone Prili; Valeria Bragaglia; Vara Prasad Jonnalagadda; Jesse Luchtenveld; Bart J. Kooi; Fabrizio Arciprete; Abu Sebastian; Ghazi Sarwat Syed (Advanced Materials Interfaces, 2025)
Abstract Highly textured chalcogenide films have recently gained significant interest for phase‐change memory applications. Several reports have highlighted that programming efficiency improves in devices featuring superlattice stacks, such as Ge2Sb2Te5/Sb2Te3. However, to be technologically relevant, these films must be deposited on foundry‐scale wafers using processes compatible with back end of the line (BEOL) integration and complementary metal‐oxide‐semiconductor (CMOS) technology, such as, for example, sputter deposition. In this work, we present our observations on the influence of temperature, pressure, and seeding layer on the sputter growth processes of superlattice films. By measuring various material properties, we construct a pseudo‐phase diagram to illustrate the growth of both individual and superlattice films with different periodicities on technologically relevant substrates, namely SiO2 and carbon. These results provide important insights into the structure, intermixing and electro‐optical properties of superlattice films, and identify optimal growth parameters critical for the manufacturability via sputtering of the material.